Use of exercise by bulimic women in treatment - Stafslien, Barbara F. (My University, 1986)
Exercise practices of bulimic women in treatment were investigated using a questionnaire developed by the researcher. Twenty-six women diagnosed and currently receiving treatment for bulimia at the Regional Clinic for Eating Disorders participated in the study. Ninety-six percent of the group reported binge-eating behaviors with a mean frequency of 20.1 times/month. Forty-six percent of the group reported vomiting behaviors with a mean frequency of 26.6 times/month. Eighty-five percent of the group reported using exercise as a method of weight loss. Percentages reported were similar to those of other researchers. The primary motivations for exercising included the following: a) weight control, b) to lift spirits or for emotional well-being, and c) to improve body appearance. The primary influences of current exercise practices were friends, television, and magazines. The mean exercise duration was 556 minutes/week, well above the American College of Sports Medicine (ACSM) minimum recommendations of 20 to 30 minutes at least three days per week at 65 percent of maximal heart rate for conditioning or maintaining cardiovascular fitness. The mean rate of perceived exertion was 14, just above the ACSM recommended minimum of 12 to 13 for conditioning and maintenance of cardiovascular fitness.
Keywords: Exercise -- Psychological aspects; Bulimia